Biological applications of biosynthesized silver nanoparticles through the utilization of plant extracts - Rouhollah Heydari * (Lorestan University of Medical Sciences, 2017)
Widespread uses of metallic nanoparticles, especially silver nanoparticles (AgNPs) in biology, pharmaceuticals, and medicine lead to the development of biosynthesis methods that are in turn utilized to prepare these nanoparticles. Among the biosynthesis methods, which are used to prepare nanoparticles, the plant-mediated methods have gained great attention due to several advantages such as cost-effectiveness, availability, eco-friendliness and nontoxicity of plants. Moreover, plant extracts are rich in different compounds which act as inhibitory and capping agents. For these reasons, plant-mediated methods can be potentially used for large-scale production of nanoparticles with different properties. The present article focuses on plant-mediated AgNPs using various plants and their biological applications such as antimicrobial, antioxidant, anticancer, anti-inflammatory, hepatoprotective and antilarvicidic properties.